Domestic Waste Management Based on Collaborative Governance in Pekanbaru City - Suryani Suryani (Universitas Sultan Ageng Tirtayasa, 2022)
Waste management in Pekanbaru City is not optimal, this can be seen from the many piles of garbage on the side of roads, rivers, and bridges this is because there is still a lack of public awareness of cooperation in managing domestic waste in the city of Pekanbaru. stakeholders in domestic waste management is a collaboration involving the government, the private sector and the community in managing domestic waste in Pekanbaru City. This study aims to determine collaborative governance in the management of domestic waste in Pekanbaru City, and to determine the factors that hinder the collaboration of stakeholders in the management of domestic waste. This study uses a descriptive qualitative approach with data collection techniques in-depth interviews, documentation studies and observations. Data analysis was carried out by reducing data, analyzing data, presenting data and drawing conclusions. The results of the study found The results showed that waste management in Pekanbaru City still uses conventional methods, namely by sorting, collecting, transporting, processing, and final processing by sending it to the collaborative Muara Fajar Rumbai Pesisir Final Disposal Site. The study also concluded that Stakeholders in the management of domestic waste in the city of Pekanbaru were not optimal, this was due to several inhibiting factors such as the absence of work programs and the lack of awareness to collaborate in the management of domestic waste in the city of Pekanbaru.